Environmental enrichment and the sensory brain: the role of enrichment in remediating brain injury - Alwis, Dasuni S. (Frontiers Media S.A., 2014)
The brain's life-long capacity for experience-dependent plasticity allows adaptation to new environments or to changes in the environment, and to changes in internal brain states such as occurs in brain damage. Since the initial discovery by Hebb (1947) that environmental enrichment (EE) was able to confer improvements in cognitive behavior, EE has been investigated as a powerful form of experience-dependent plasticity. Animal studies have shown that exposure to EE results in a number of molecular and morphological alterations, which are thought to underpin changes in neuronal function and ultimately, behavior. These consequences of EE make it ideally suited for investigation into its use as a potential therapy after neurological disorders, such as traumatic brain injury (TBI). In this review, we aim to first briefly discuss the effects of EE on behavior and neuronal function, followed by a review of the underlying molecular and structural changes that account for EE-dependent plasticity in the normal (uninjured) adult brain. We then extend this review to specifically address the role of EE in the treatment of experimental TBI, where we will discuss the demonstrated sensorimotor and cognitive benefits associated with exposure to EE, and their possible mechanisms. Finally, we will explore the use of EE-based rehabilitation in the treatment of human TBI patients, highlighting the remaining questions regarding the effects of EE.